Le Massif du Taburno-Camposauro, une montagne calcaire en position de charnière à l'échelle de l'Apennin méridional (Italie du Sud) - Bruno Comentale (Physio-Géo)
The Taburno-Camposauro limestone faulted block has a key location between tyrrhenian and adriatic sides of the Southern Apennines, because of the relief disruption due to extensional Plio-Pleistocene neotectonics. From this, results a contrasted landscape, with prior gentle erosional landsurfaces (Upper Miocene-Early Pliocene?) subsequently disrupted by huge fault scarps. After a microtectonic analysis along these fault scarps, also considering the deformation of breccia – which are regarded as genetically linked with the erosional landsurfaces shaping –, the discussion deals with the regional geomorphic pattern, mainly the nearest Matese mountain.